Speech Intelligibility in Virtual Avatars: Comparison Between Audio and Audio–Visual-Driven Facial Animation - Federico Cioffi; Massimiliano Masullo; Aniello Pascale; Luigi Maffei (Acoustics)
Speech intelligibility (SI) is critical in effective communication across various settings, although it is often compromised by adverse acoustic conditions. In noisy environments, visual cues such as lip movements and facial expressions, when congruent with auditory information, can significantly enhance speech perception and reduce cognitive effort. In an ever-growing diffusion of virtual environments, communicating through virtual avatars is becoming increasingly prevalent, thus requiring a comprehensive understanding of these dynamics to ensure effective interactions. The present study used Unreal Engine’s MetaHuman technology to compare four methodologies used to create facial animation: MetaHuman Animator (MHA), MetaHuman LiveLink (MHLL), Audio-Driven MetaHuman (ADMH), and Synthetized Audio-Driven MetaHuman (SADMH). Thirty-six word pairs from the Diagnostic Rhyme Test (DRT) were used as input stimuli to create the animations and to compare them in terms of intelligibility. Moreover, to simulate a challenging background noise, the animations were mixed with a babble noise at a signal-to-noise ratio of −13 dB (A). Participants assessed a total of 144 facial animations. Results showed the ADMH condition to be the most intelligible among the methodologies used, probably due to enhanced clarity and consistency in the generated facial animations, while eliminating distractions like micro-expressions and natural variations in human articulation.